Ficus vogelii methanol leaf extract ameliorates inflammation and arthritis by modulating osmotic fragility in C57BL/6J mice (Nigerian Journal of Physiological Sciences, 2021)
The study evaluated the membrane-stabilizing potentials in red blood cells and anti-inflammatory properties in C57BL/6J mice of the methanol leaf extract of Ficus vogelii. Animals were treated orally with different doses of the extract (50, 100, 200 mg/kg) for 30 days and their blood was measured for membrane stability at different saline concentrations. Diclofenac (12.5 mg/kg) or Indomethacin (10 mg/kg) was used as standard in the anti-inflammatory studies. The mean corpuscular fragility (MCF) values and their corresponding percentage stabilization increased significantly (p≤0.05) in the treatment groups compared to the negative control. Treatment of mice with 50, 100 and 200 mg/kg of the extract significantly (p≤0.05) inhibited carrageenan-induced paw oedema in mice. The highest dose (200 mg/kg) showed lower anti-inflammatory activity compared to Diclofenac (12.5 mg/kg). Daily administration of the extract significantly (p≤0.05) suppressed adjuvant-induced paw arthritis by day 15 and 30 post arthritis induction. Ficus vogelii extract inhibited granuloma formation significantly. The anti-inflammatory effects of methanol leaf extract of Ficus vogelii on granuloma formation were comparable to that of Indomethacin (10 mg/kg). In summary, this study showed that the methanol leaf extract of Ficus vogelii possessed membrane-stabilizing potentials and anti-inflammatory properties, therefore, providing further proof that the leaves contain an active compound with potent anti-inflammatory activity